2016
DOI: 10.1111/jfpe.12371
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lemon Marmalade Formulated with New Sweeteners (Isomaltulose and Tagatose): Effect on Antioxidant, Rheological and Optical Properties

Abstract: The aim of this study was to make lemon marmalades in which sucrose is replaced by sweeteners such as tagatose and isomaltulose. Analyses of Brix, pH, moisture, water activity, antioxidant capacity, optical and rheological properties were carried out on marmalades on their first day of storage, and after 60 days of storage. Microbiological analyses were also performed. Moreover, a sensory evaluation was performed to assess its consumer acceptance as compared to marmalade made with sucrose. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…However, it is metabolized differently, has a minimal effect on blood glucose and insulin levels, 2 Journal of Food Quality and also provides a prebiotic effect [9,11]. It can be used in ready-to-eat cereals, diet soft drinks, frozen yoghurt/nonfat ice cream, soft/hard confectionary, and marmalades [12][13][14]. The unabsorbed tagatose is fermented in the colon, where it acts as soluble fibre [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is metabolized differently, has a minimal effect on blood glucose and insulin levels, 2 Journal of Food Quality and also provides a prebiotic effect [9,11]. It can be used in ready-to-eat cereals, diet soft drinks, frozen yoghurt/nonfat ice cream, soft/hard confectionary, and marmalades [12][13][14]. The unabsorbed tagatose is fermented in the colon, where it acts as soluble fibre [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Rubio‐Arraez et al. (2017), the manufacture of lemon marmalade was performed, in which sugar was replaced by the combination of sweeteners (Isomaltulose and Tagatose) in different proportions. The tested formulations were compared with a control sample (100% sucrose).…”
Section: Resultsmentioning
confidence: 99%
“…With the results of this review, it can be observed that blends of different sweeteners are in general almost always favorable to the sensory aspects of sweet fruit preserves with partial or completely sugar reduction, with highlights for some positive outcomes using blends of natural sweeteners with artificial ones (Akesowan & Choonhahirun, 2014; Riedel et al., 2015; Santos et al., 2014; Souza et al., 2013), blends of artificial sweeteners (Lago‐Vanzela et al., 2011), or blends with natural bulk sweeteners (Farias et al., 2019; Lago‐Vanzela et al., 2011; Minh, 2020; Rubio‐Arraez, Capella, Castelló, et al., 2016; Rubio‐Arraez, Capella, Ortola, et al., 2016, Rubio‐Arraez et al., 2017; Rubio‐Arraez et al., 2018; Riedel et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…discovered that overall acceptability was mainly determined by the taste, and possibly the color of apple jellies, but not by their texture and spreadability. Instead, spreadability is an important variable commonly measured in gels; for example, lemon marmalade, berry marmalades, black‐plum jams and fluted pumpkin jams because the microstructure of mixed gels had an essential role in sensory perception…”
Section: Resultsmentioning
confidence: 99%